Synthesis of MXene Composites Using Thiourea as a Nitrogen–Sulfur Precursor - Junming Zhang; Yefeng Feng; Junhao Peng; Kaidan Wu; Zuyong Feng; Miao He; Kunhua Wen; Deping Xiong (Crystals)
In potassium ion electrode materials, MXenes have garnered significant attention in the energy storage field due to their high conductivity and complex surface chemistry. In this work, thiourea was used as a nitrogen–sulfur composite precursor, and a self-assembly method was employed to synthesize a material, named nitrogen–sulfur– MXene (NS-MXene). During the reaction, thiourea molecules attach to the surface and interlayers of MXene, increasing the interlayer spacing. Upon heating, thiourea molecules decompose into nitrogen (N) and sulfur (S), which then combine with the MXene material. The N and S provide additional capacity for potassium ion storage, while the increased interlayer spacing also facilitates the intercalation and deintercalation of K+. Use of NS-MXene as anode material for potassium-ion batteries results in a high-rate performance (final capacity of 205.2 mAhg−1 at 0.1 Ag−1), long-term cycling stability (128.5 mAhg−1 at 0.5 Ag−1), and a good specific capacity (141 mAhg−1 at 0.1 Ag−1). This groundbreaking discovery opens the door to investigating MXene-based energy storage materials with superior performance and creates a new standard for MXene derivatives.